"Glokalizacija" ali getoizacija lokalne demokracije? - Mlinar, Zdravko (Teorija in praksa, 2000)
In the time when people in local and regional units of developed countries as co-responsible increasingly take part in solving national and global social issues, the legal order of Slovenian state spatially and substantively limits their role to narrow local affairs. But "purely local" affairs are in decline and considering that the size of the municipalities was reduced, this implies the impowerishment of the local self-government. Thus what is happening within the territoral organization of the Slovenian state seems to be getoization, a kind of exclusion, rather than glocalization, i. e. broadening and enrichment of local democracy. Today, with broadening accessibility, new possibilities for direct involvement are opening up. However, in Slovenia a pronounced separation of direct and representative democracy has been established which does not fit the information age. In this context, the background of the conflict which appeared due to the demand of the constitutional court to (sub-)divide the municipality of Koper, becomes more understandable. At the same time, the present changes in the area of Slovenian Istria reveals how the obsolete state-centric mentality, which was the starting point of the weakenning all narrower territorial units in order to strenghten the unity of the country as a whole vis a vis the potential external threat, absurdly perverts into its opposition.
Keywords: sociologija; sociology; prostorska sociologija; local government; lokalna samouprava; lokalna uprava; teritorialna razdelitev; lokalizem; glokalizacija; Slovenia; Slovenija; Slovenska Istra; Slovenian Istria